2002
DOI: 10.1108/14691930210424761
|View full text |Cite
|
Sign up to set email alerts
|

Intellectual capital and business start‐up success

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
206
0
26

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 275 publications
(237 citation statements)
references
References 19 publications
5
206
0
26
Order By: Relevance
“…Broadly, IC represents the intangible assets companies leverage for their competitive advantage (Bontis, 1996(Bontis, , 1998(Bontis, , 2001Sveiby, 1997;Petty & Guthrie, 2000;Hormiga, Batista-Canino, & Sánchez-Medina, 2011). Some entrepreneurship scholars referred to IC regarding start-ups (Peña, 2002;Hayton, 2005;Hormiga et al, 2011;Link & Ruhm, 2011;Musteen & Ahsan, 2013) and provided useful implications for investigating entrepreneurial intentions as well (Matricano, 2016).…”
Section: Theoretical Framework and Research Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…Broadly, IC represents the intangible assets companies leverage for their competitive advantage (Bontis, 1996(Bontis, , 1998(Bontis, , 2001Sveiby, 1997;Petty & Guthrie, 2000;Hormiga, Batista-Canino, & Sánchez-Medina, 2011). Some entrepreneurship scholars referred to IC regarding start-ups (Peña, 2002;Hayton, 2005;Hormiga et al, 2011;Link & Ruhm, 2011;Musteen & Ahsan, 2013) and provided useful implications for investigating entrepreneurial intentions as well (Matricano, 2016).…”
Section: Theoretical Framework and Research Hypothesesmentioning
confidence: 99%
“…IC is made up of human capital, structural capital, and relational capital (Sullivan, 1999;Brennan & Connell, 2000;Petty & Guthrie, 2000;Sanchez, Chamichade, & Olea, 2000;Roos, Brainbridge, & Jacobsen, 2001;Peña, 2002;Kaufmann & Schneider, 2004;Boedker, Guthrie, & Cuganesan, 2005;Hormiga et al, 2011;Musteen & Ahsan, 2013). By human capital, management scholars refer to intellectual agility, knowledge and personal capabilities (Bontis, 1998;Bontis, Dragonetti, Jacobsen, & Roos, 1999;Bontis, Keow, & Richardson, 2000;Khalique, Bontis, Shaari, & Isa, 2015;Subramaniam & Youndt, 2005;Montequín, Fernández, Cabal, & Gutierrez, 2006;Tovstiga & Tulugurova, 2007;Wu, Chang, & Chen, 2008;Hsu & Fang, 2009).…”
Section: Theoretical Framework and Research Hypothesesmentioning
confidence: 99%
“…Research in this area highlights the value added through relational capital, for example, in building reputation with clients, suppliers and other stakeholders. Further, the emotional support and active participation by family, friends and the entrepreneur's personal network are also linked to new venture success (Pena, 2002;Hormiga, BatistaCanino and Sanchez-Medina, 2011). As noted, a novel finding of the current study is that, controlling for the number of competencies in each category, an analysis of average influence scores in the full sample revealed that interpersonal skills had the highest average influence score.…”
Section: Interpersonal Skillsmentioning
confidence: 99%
“…Networking, deal making and emotional intelligence are aligned to the development of relational capital which emphasizes the development of productive business networks (Pena, 2002). Hormiga et al (2011) describe relational capital as the value generated by entrepreneurs via their relations with suppliers, customers, investors but equally with internal stakeholders in their organisation and friends and family (Gately and Cunningham, 2014b).…”
Section: Interpersonal Skillsmentioning
confidence: 99%
“…It seems that the level of education can in luence the failure rate of start-up irms and the intellectual capital can be associated with the decision to repeat the entrepreneurial experience. The in luence of education on the business performance was also examined by Pena (2002). The results of his study suggest that the human capital (education, competencies and motivations) plays a crucial role in the success of a business.…”
Section: Resultsmentioning
confidence: 99%